G protein–coupled estrogen receptor: a promising therapeutic target for aldosterone-induced hypertension - Li, Xuehan; Kuang, Wenlong; Qiu, Zhihua; Zhou, Zihua (Frontiers in Endocrinology, 2023)
Aldosterone is one of the most essential hormones synthesized by the adrenal gland because it regulates water and electrolyte balance. G protein-coupled estrogen receptor (GPER) is a newly discovered aldosterone receptor, which is proposed to mediate the non-genomic pathways of aldosterone while the hormone simultaneously interacts with mineralocorticoid receptor. In contrast to its cardio-protective role in postmenopausal women via its interaction with estrogen, GPER seems to trigger vasoconstriction effects and can further induce water and sodium retention in the presence of aldosterone, indicating two entirely different binding sites and effects for estrogen and aldosterone. Accumulating evidence also points to a role of aldosterone in mediating hypertension and its risk factors via the interaction with GPER. Therefore, with this review, we aimed to summarize the research on these interactions to help (1) elucidate the role of GPER activated by aldosterone in the blood vessels, heart, and kidney; (2) compare the non-genomic actions between aldosterone and estrogen mediated by GPER; and (3) address the potential of GPER as a new promising therapeutic target for aldosterone-induced hypertension.